LEMBAGA ARBITRASE ISLAM DI INDONESIA - Yusna Zaidah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
A dispute is a social problem thatdirectly in contact with the law and require solving integrally. Each order of society has various ways to get agreement in the proceedings or to resolve disputes among them. The People nowadays are starting to abandon habitual ways resorting to formal ways provided by law that are recognized by the state. There are various kinds of way to dispute in the society that each has particular strengths and weaknesses, one of them is arbitration. In Indonesia, National Sharia Arbitration Board as one of the institutions that offering arbitration services to the business sector economics Islam or business based on sharia.Keywords : Arbitration, Dispute, Basyarnas.